Sericin-based full-biodegradable composite film material and preparation method thereof

By combining sericin with a fully biodegradable plastic substrate and improving compatibility by using modification methods, sericin-based fully biodegradable composite film materials with excellent biodegradability and good mechanical properties were prepared, and the existing solutions were solved Poor material compatibility and unused resources.

CN119391145APending Publication Date: 2025-02-07ZHEJIANG SCI TECH UNIV SHAOXING KEQIAO RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411278997.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The poor compatibility of existing PLA and PBAT biodegradable plastic materials limits the improvement of PBAT on PLA toughness, and the resources of sericin in silk are not effectively utilized, resulting in environmental pollution and waste of resources.

Method used

Sericin is combined with all biodegradable plastics (such as PBAT and PLA), and the sericin-based fully biodegradable composite film material is prepared by vacuum drying and melt kneading extrusion. The sericin is modified to improve its combination with Compatibility of plastic.

Benefits of technology

It has achieved excellent biodegradability and good mechanical properties of sericin-based fully biodegradable composite materials, is easy to process, has good economic benefits and broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391145A_ABST
    Figure CN119391145A_ABST
Patent Text Reader

Abstract

The invention discloses a sericin-based full-biodegradable composite film material and a preparation method thereof. The composite film material is prepared from 0-90 parts of a full-biodegradable plastic base, 10-40 parts of sericin and 0.1-10 parts of an additive. The preparation method comprises the following steps: (1) carrying out vacuum drying on the full-biodegradable plastic base and the sericin at 60 DEG C for 18-24 hours; (2) mixing the dried sericin with an additive in a preset proportion to obtain a sericin mixture; and (3) mixing the sericin protein mixture with the full-biodegradable plastic base, and carrying out melt mixing extrusion granulation, injection molding or extrusion forming on a twin-screw extruder at 140-160 DEG C to obtain a target product. The sericin-based full-biodegradable composite material prepared by the preparation method disclosed by the invention has excellent biodegradability and good mechanical properties and is easy to process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of plastic materials, and in particular relates to a sericin-based fully biodegradable composite film material and a preparation method thereof. Background Art

[0002] In recent years, traditional petrochemical-based plastics are gradually being replaced by biodegradable and reusable bio-based materials known as "green materials". Currently, the most important and widely used biodegradable polymers are aliphatic polyesters and proteins, such as polylactic acid (PLA), polybutylene adipate / terephthalate (PBAT), etc.

[0003] Polylactic acid (PLA) is an aliphatic polyester made from crops such as corn, fermented to obtain lactic acid, and then prepared through a series of chemical synthesis. It can eventually be decomposed into carbon dioxide and water, and is a typical biodegradable plastic. Polylactic acid has good thermal stability, biocompatibility, gloss, transparency, feel and heat resistance, and also has certain bacteria resistance, flame retardancy and UV resistance. Therefore, it has a wide range of uses and can be applied to various plastic products, packaged food, fast food lunch boxes, non-woven fabrics, industrial and civilian fabrics, agricultural fabrics, health fabrics, rags, sanitary products, outdoor UV protection fabrics, tent fabrics, floor mats, disposable infusion equipment, and non-disassembly surgical sutures. Although pure PLA has the advantages of high transparency and high gloss, its disadvantages such as hardness and brittleness, difficulty in processing and poor thermal stability affect its application in injection molding.

[0004] Polybutylene adipate / terephthalate (PBAT), also known as polybutylene adipate / terephthalate, is a copolymer of butylene adipate and terephthalate. It has the characteristics of polybutylene adipate-1,4-diol (PBA) and polybutylene terephthalate (PBT), and is a thermoplastic biodegradable plastic. PBAT has good ductility and elongation at break, as well as good heat resistance and impact resistance. In addition, PBAT also has excellent biodegradability, and is currently one of the most active biodegradable materials in the research of biodegradable plastics and the best market application.

[0005] Although both PLA and PBAT have unique properties, experiments show that PLA has high strength but poor flexibility, while PBAT has low strength but good toughness. If the advantages of the two can be combined and complemented, a PLA / PBAT biodegradable composite material with good performance can be prepared. However, PLA and PBAT are an incompatible two-phase system, and the dispersed phase PBAT will be dispersed in the PLA matrix with a larger particle size, and PBAT and PLA have poor compatibility, which greatly limits the effect of PBAT on improving the toughness of PLA. Therefore, it is necessary to improve the compatibility of the two, and by modifying PBAT and PLA, improve the interfacial compatibility of the two, so as to obtain a composite material with better performance and more stability.

[0006] Silk is a natural protein filament with a soft and smooth feel, soft luster, bright color and strong hygroscopicity. Due to its health, comfort, unique silk sound effect and noble and gorgeous appearance, it is known as the "Queen of Fibers" and is widely used in clothing and decorative materials. Silk is mainly composed of two proteins with different properties, fibroin and sericin. For a long time, the part of silk that has been truly applied is fibroin, which is mainly used as a raw material for clothing, and has also been widely developed and utilized in other fields. However, the outer layer of sericin in silk is mostly removed and discharged directly. The content of sericin in silk is about 20-30%, and its degumming rate is usually around 20%. With the current production technology, 150-250kg of sericin will be lost with the production wastewater for every 1t of cocoon processed, resulting in a serious excess of organic matter such as sericin in the silk production wastewater, a large amount of dissolved oxygen in the water is consumed, and the water body is eutrophic and loses its self-purification ability. This not only pollutes the environment, but also is a great waste of sericin, a natural protein resource. Sericin is a natural protein with a very high nitrogen content and is a very good agricultural fertilizer. Mixing it with degradable plastic materials to prepare protein-based degradable composite film materials has positive significance for energy conservation, emission reduction, low-carbon and environmental protection. Summary of the invention

[0007] The object of the present invention is to provide a sericin-based fully biodegradable composite film material and a preparation method thereof. In view of the defects in the prior art, the sericin-based fully biodegradable composite material prepared by the present invention has excellent biodegradability, good mechanical properties and is easy to process.

[0008] In order to solve the above technical problems, the following technical solutions are adopted:

[0009] A sericin-based fully biodegradable composite film material, characterized in that the composite film material consists of 0-90 parts of a fully biodegradable plastic base, 10-40 parts of sericin, and 0.1-10 parts of an additive.

[0010] Preferably, the fully biodegradable plastic base includes polybutylene adipate-terephthalate (PBAT), polylactic acid (PLA) or a mixture of the two.

[0011] Preferably, the sericin includes unhydrolyzed sericin and hydrolyzed sericin.

[0012] Preferably, the additive includes one or two or more of water, glycerol, chain extender ADR, polyethylene glycol 400, maleic anhydride grafted modified PBAT (MAH-g-PBAT), and glycidyl methacrylate / maleic anhydride copolymer grafted modified PBAT (GMA / MAH-g-PBAT).

[0013] A method for preparing a sericin-based fully biodegradable composite film material, characterized by comprising the following steps:

[0014] (1) drying the fully biodegradable plastic base and sericin at 60° C. in a vacuum oven for 18 to 24 hours;

[0015] (2) mixing the dried sericin with an additive in a predetermined proportion to obtain a sericin mixture;

[0016] (3) The sericin mixture is then mixed with a fully biodegradable plastic base, and then melt-mixed and extruded on a twin-screw extruder at 140° C. to 160° C. to obtain a target product.

[0017] Preferably, the fully biodegradable plastic base includes PBAT, PLA or a mixture of the two.

[0018] Preferably, the sericin includes unhydrolyzed sericin and hydrolyzed sericin.

[0019] Preferably, the additive includes one or two or more of water, glycerol, chain extender ADR, polyethylene glycol 400, maleic anhydride grafted modified PBAT, and glycidyl methacrylate / maleic anhydride copolymer grafted modified PBAT.

[0020] Preferably, the sericin is modified sericin, and the modification method thereof comprises:

[0021] a. Silk degumming under high temperature and high pressure: degumming the raw silk, and taking the degumming liquid after the degumming is completed;

[0022] b. Preparation of pure sericin powder: The collected degumming liquid was rotary evaporated at 80°C to obtain sericin concentrate, which was then powdered using a spray dryer;

[0023] c. Preparation of modified sericin: sericin powder, sodium sulfite and urea solution were mixed and pretreated with magnetic stirring in a water bath at 50°C for 30 minutes; after the temperature was raised to 80°C, a certain amount of glycidyl methacrylate and initiator ammonium persulfate were added, and the reaction was kept warm for several hours to generate modified sericin; the product was first washed with acetone and centrifuged twice, and then repeated with anhydrous ethanol twice at a speed of 4000r / min for 10min; after filtration, the filter cake was vacuum dried at 40°C for 12h and then sealed for storage.

[0024] After optimization, the powder is prepared by spray drying in step b, and the air inlet temperature is set to 180°C, the air outlet temperature is set to 80-85°C, and the centrifugal speed is set to 24000r / min.

[0025] The above technical solution has the following beneficial effects:

[0026] The sericin-based fully biodegradable composite material of the present invention has excellent biodegradability, good mechanical properties and is easy to process. The present invention also discloses a method for preparing the sericin-based fully biodegradable composite material, which can be realized by using an existing twin-screw extruder, is easy to implement, has strong operability, is easy to industrialize and mass produce, and has good economic benefits and broad application prospects.

[0027] Compared with traditional synthetic plastic products, biodegradable synthetic plastics are superior to ordinary synthetic plastic products in terms of light transmittance, oxygen permeability, heat resistance, toughness, softness, elasticity, tensile strength and anti-aging performance. The oxygen permeability of biodegradable plastic film produced by melt extrusion is as low as 0.8 (mlmm) / (m2·d·Pa), the water permeability is as low as 1.9 / (ms·Pa), the tensile strength can reach 22MPa, and the elongation is as high as 380.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention will be further described below in conjunction with the accompanying drawings:

[0029] Figure 1 The following are soil buried photos showing the changes in the film.

[0030] Figure 2 Infrared spectra of GMA, GMS and Sericin.

[0031] Figure 3 Contact angle diagram of Sercin and GMS with different grafting rates.

[0032] Figure 4 SEM images of Sericin and GMS.

[0033] Figure 5 TG curves (a) and DTG curves (b) of Sericin and GMS with different grafting rates.

[0034] Figure 6 DSC curves of Sericin and GMS with different grafting rates. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is described in detail below in conjunction with specific embodiments:

[0036] Example 1

[0037] A sericin-based fully biodegradable composite film material, the components are proportioned by weight percentage:

[0038] 2 parts of PLA, 87.8 parts of PBAT, 10 parts of sericin powder, and 0.2 parts of chain extender ADR. Polylactic acid was purchased from Zhejiang Hisun Biomaterials Co., Ltd., PBAT was purchased from Xinjiang Blue Mountain Tunhe Polyester Co., Ltd., sericin powder came from Dali Silk (Zhejiang) Co., Ltd., and chain extender ADR was purchased from BASF of Germany.

[0039] The preparation method of the sericin-based fully biodegradable material comprises the following steps:

[0040] 1) PLA, PBAT and sericin powder were vacuum dried at 60°C for 18-24h respectively;

[0041] 2) taking the dried PLA, PBAT and sericin powder and mixing them with the chain extender ADR in a predetermined ratio and adding them into the feeding port of the twin-screw extruder;

[0042] 3) Through three-stage temperature control, at a temperature of 140°C to 160°C, a twin-screw extruder performs melt mixing, extrusion and granulation, and molds the resulting film into a 0.05 mm film on a flat vulcanizer.

[0043] Example 2

[0044] A sericin-based fully biodegradable composite film material, the components are proportioned by weight percentage:

[0045] 2 parts of PLA, 80 parts of PBAT, 20 parts of sericin powder, and 3 parts of maleic anhydride grafted modified PBAT (MAH-g-PBAT). Polylactic acid was purchased from Zhejiang Hisun Biomaterials Co., Ltd., PBAT was purchased from Xinjiang Blue Mountain Tunhe Polyester Co., Ltd., sericin powder came from Dali Silk (Zhejiang) Co., Ltd., and MAH-g-PBAT was homemade.

[0046] The preparation method of the sericin-based fully biodegradable composite film material comprises the following steps:

[0047] 1) PLA, PBAT and sericin powder were vacuum dried at 60°C for 18-24h respectively;

[0048] 2) Mixing the sericin powder and MAH-g-PBAT at high speed and leaving for one hour to obtain a sericin powder mixture.

[0049] 3) taking the dried mixture of PLA, PBAT and sericin powder and mixing them in a predetermined ratio and adding them to the feeding port of the twin-screw extruder;

[0050] 4) The mixture is melt-mixed and extruded into granules at 140°C to 160°C on a twin-screw extruder through three-stage temperature control, and then molded into a 0.05 mm film on a flat vulcanizer.

[0051] Example 3

[0052] A sericin-based fully biodegradable composite film material, the components are proportioned by weight percentage:

[0053] 2 parts of PLA, 85 parts of PBAT, 10 parts of sericin powder, 3 parts of glycidyl methacrylate / maleic anhydride copolymer graft-modified PBAT (GMA / MAH-g-PBAT). Polylactic acid was purchased from Zhejiang Hisun Biomaterials Co., Ltd., PBAT was purchased from Xinjiang Lanshan Tunhe Polyester Co., Ltd., sericin powder was from Dali Silk (Zhejiang) Co., Ltd., and GMA / MAH-g-PBAT was homemade.

[0054] The preparation method of the sericin-based fully biodegradable composite film material comprises the following steps:

[0055] 1) PLA, PBAT and sericin powder were vacuum dried at 60°C for 18-24h respectively;

[0056] 2) The sericin powder and GMA / MAH-g-PBAT were mixed by high-speed stirring and allowed to stand for one hour to obtain a sericin powder mixture.

[0057] 3) taking the dried mixture of PLA, PBAT and sericin powder and mixing them in a predetermined ratio and adding them to the feeding port of the twin-screw extruder;

[0058] 4) The mixture is melt-mixed and extruded into granules at 140°C to 160°C on a twin-screw extruder through three-stage temperature control, and then molded into a 0.05 mm film on a flat vulcanizer.

[0059] The film samples obtained from Examples 1 to 3 were tested.

[0060] Mechanical test: Referring to the national standard GBT35795-2017 fully biodegradable agricultural ground covering film, tensile strength and elongation at break were tested on a universal mechanical testing machine. The test was stretched at 500 mm / min until the specimen broke. The maximum tensile load was measured with an accuracy of 0.01 N. The test was repeated 5 times and the average value was taken.

[0061] Degradability test: Put the sample into a 0.01mol / L NaOH solution in a conical flask. After 28 days, take out the sample and wash it with deionized water. After absorbing the water on the surface of the sample with filter paper, place it in an electric vacuum drying oven and dry it at 40°C for 48 hours. Weigh it with an electronic balance. The sample degradation rate is calculated by the weight loss rate w of the material, w = (w0-wt) / w, w0 is the initial mass of the sample, wt is the mass of the sample at time t, and the nitrogen release of the corresponding solution is tested at the same time.

[0062] The test results are shown in the table below.

[0063] Breaking strength / N Elongation at break / % Weight loss rate / % Nitrogen release / (mg / L) Example 1 10.58 764.60 5.99 16.42 Example 2 9.65 718.22 11.89 32.34 Example 3 7.92 517.75 4.61 12.74

[0064] Buried photos

[0065] The blended film of PLA and PBAT without any additives was used as a blank group, and Examples 1 to 3 were used as a control group. The surface changes of the films were shown in FIG. Figure 1 As shown, Scheme 1, Scheme 2 and Scheme 3 are Embodiment 1, Embodiment 2 and Embodiment 3.

[0066] According to the above table and Figure 1 It can be seen that the tensile strength of the film products obtained in Examples 1 to 3 can reach up to 10.58N, and the elongation at break can reach 764.60%. At the same time, by observing the surface of the film buried in the soil, it can be found that the addition of sericin accelerates the degradation of the film. This shows that the film product prepared by the present invention has good mechanical properties and excellent biodegradability.

[0067] The sericin powder used in Examples 1 to 3 is modified sericin powder, and the modification method thereof includes:

[0068] a. High temperature and high pressure degumming of silk: subject the raw silk to high temperature and high pressure degumming. After the degumming is completed, take the degumming liquid.

[0069] b. Preparation of pure sericin powder: The collected degumming liquid was rotary evaporated at 80°C to obtain sericin concentrate, which was then powdered using a spray dryer with the inlet air temperature set at 180°C, the outlet air temperature at 80-85°C, and the centrifugal speed at 24,000 r / min.

[0070] c. Preparation of modified sericin: 2 parts of sericin powder, 0.35 parts of sodium sulfite and 8 parts of urea solution were mixed, and pretreated with magnetic stirring in a 50°C water bath for 30 minutes; after the temperature rose to 80°C, a certain amount of glycidyl methacrylate (GMA) and initiator ammonium persulfate (APS) were added, and the reaction was kept warm for several hours to generate modified sericin (GMA-g-Sericin, referred to as GMS); the product was first washed with acetone and centrifuged twice, and then repeated twice with anhydrous ethanol at a speed of 4000r / min for 10min; after filtration, the filter cake was vacuum dried at 40°C for 12h and then sealed for storage.

[0071] 1. Infrared spectroscopy analysis of modified sericin

[0072] Figure 2 The FT-IR infrared spectra of monomer GMA, modified sericin (GMS) and sericin (Sericin) are shown in Figure 5. Compared with the infrared spectra of original sericin and GMA, the grafted product GMS showed new absorption peaks at 1731.99 cm-1 and 907.19 cm-1

[59] . The former is the characteristic vibration frequency absorption peak of the ester group C=O, and the latter is the characteristic vibration frequency absorption peak of the epoxy group. This proves that GMA is grafted onto sericin.

[0073] 2. Hydrophobicity analysis of modified sericin

[0074] The contact angle can reflect the hydrophobicity of the surface of an object. According to Young's equation, a contact angle less than 90° is hydrophilic, and a contact angle greater than 90° is hydrophobic. There are a large number of hydrogen bonds in the sericin molecule, which causes some groups inside the molecular chain to agglomerate due to hydrogen bonding. After pretreatment with sodium sulfite and urea, its spatial structure is disintegrated, showing more reaction sites. The double bond of GMA is grafted on the reaction site, and the epoxy group and CH hydrophobic group at the other end are exposed, showing hydrophobicity. Figure 3 As shown, the contact angle of the unmodified sericin is 61.7°, and the contact angles of the modified sericin with GP% of 34.32% and 47.63% are 84.2° and 97.3°, respectively. The higher the grafting rate, the larger the contact angle becomes and exceeds 90°, indicating that the higher the grafting rate of the modified sericin after modification, the stronger its hydrophobicity.

[0075] 3. Scanning electron microscopy analysis of modified sericin

[0076] Figure 4a and b are SEM images of the microscopic morphology of the original sericin and the modified sericin. There are many secondary bonds in sericin, such as hydrogen bonds, van der Waals forces, ionic bonds, etc. These secondary bonds stretch the sericin into flat spheres. Moreover, the surface is smooth, and the internal active groups cannot react with the monomers. The modified sericin has its spheres opened and presents a rough layered shape. This is because the monomers are grafted onto the skeleton of the sericin molecule, and the macromolecular chains are piled up, which also proves the progress of the grafting reaction from the side.

[0077] 4. Thermogravimetric analysis of modified sericin

[0078] The thermal stability of polymers is generally analyzed by thermogravimetric analysis. Figure 5 The thermogravimetric curves of sericin, high grafting rate modified sericin (H-GMS) and low grafting rate modified sericin (L-GMS) are presented in detail. It can be seen from the figure that the thermal decomposition temperature of the modified sericin has increased. Sericin has a small weight loss peak from room temperature to 220°C, which is mainly due to the volatilization of adsorbed and crystallized water

[63] . As the temperature continues to rise, the first large weight loss peak appears at 255.4°C, the molecular chain of Sericin begins to decompose, and some amino acids with poor thermal properties begin to decompose. The decomposition reaches the fastest state at 314.1°C. The thermal properties of the modified GMS are significantly improved. The amino acid weight loss peak of L-GMS with a low grafting rate has split and shifted, and the temperature has risen to 346.9°C; the amino acid weight loss peak of H-GMS with a high grafting rate has been significantly smoothed without obvious convex points. The higher the grafting rate of GMS, the higher its maximum decomposition temperature, which increased from the original 314.1°C to 407.4°C and 413.2°C. From the changes in the thermogravimetric curve, it can be seen that grafting GMA increases the decomposition temperature of sericin, which is beneficial for its application in products that require thermal processing.

[0079] 5. Differential scanning calorimetry analysis of modified sericin

[0080] DSC is often used to study the melting and crystallization properties of polymers. Figure 6 As shown in the figure, the first endothermic peak in the DSC curve appears between 50℃ and 100℃, which is caused by water evaporation. The second endothermic peak is the thermal decomposition absorption peak of Sericin. At about 200℃, some amino acids of Sericin decompose. At the same time, it can be found that Sericin has no thermoplasticity and cannot be processed directly. The modified GMS does not have an endothermic peak at high temperature, but a crystallization exothermic peak. This is because the monomer GMA reacts with the active groups of Sericin such as -NH2 and -OH, which greatly reduces the possibility of hydrogen bonds within and between molecules. The sericin molecules that were originally tightly bound by secondary bonds such as hydrogen bonds can move or rotate, and have thermoplasticity to a certain extent.

[0081] The results of infrared spectroscopy test showed that the surface grafted product GMS had new absorption peaks at 1731.99cm-1 and 907.19cm-1. The former was the characteristic vibration frequency absorption peak of the ester group C=O, and the latter was the characteristic vibration frequency absorption peak of the epoxy group, which proved that GMA was grafted onto sericin.

[0082] Through the analysis of the contact angle results of GMS with different grafting rates, it can be seen that the addition of GMA monomer makes the originally hydrophilic protein gradually become hydrophobic.

[0083] SEM observed that the microscopic morphology of sericin before and after modification was different. After modification with GMA, the Sericin molecule changed from the original oblate sphere to a multilayered sheet. At the same time, a lot of grafted products accumulated on the surface, which was relatively rough.

[0084] Thermogravimetric and differential scanning calorimetry test results show that GMA grafted sericin significantly increases its decomposition temperature and improves heat resistance. The higher the grafting rate, the better the heat resistance, with the highest increase of nearly 100°C. At the same time, the grafted product has an obvious exothermic peak and has thermoplasticity, which is very beneficial to the thermal processing of sericin and broadens its application in thermoplastic materials.

[0085] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to solve basically the same technical problems and achieve basically the same technical effects are all included in the protection scope of the present invention.

Claims

1. A sericin-based fully biodegradable composite film material, characterized by: The composite film material consists of 0-90 parts of a fully biodegradable plastic base, 10-40 parts of sericin, and 0.1-10 parts of an additive.

2. The sericin-based fully biodegradable composite film material according to claim 1, characterized in that: The fully biodegradable plastic base includes PBAT, PLA or a mixture of the two.

3. The sericin-based fully biodegradable composite film material according to claim 1, characterized in that: The sericin includes unhydrolyzed sericin and hydrolyzed sericin.

4. The sericin-based fully biodegradable composite film material according to claim 1, characterized in that: The additives include one or two or more of water, glycerol, chain extender ADR, polyethylene glycol 400, maleic anhydride grafted modified PBAT, and glycidyl methacrylate / maleic anhydride copolymer grafted modified PBAT.

5. A method for preparing a sericin-based fully biodegradable composite film material, characterized in that The steps include: (1) drying the fully biodegradable plastic base and sericin at 60° C. in a vacuum oven for 18 to 24 hours; (2) mixing the dried sericin with an additive in a predetermined proportion to obtain a sericin mixture; (3) The sericin mixture is then mixed with a fully biodegradable plastic base, and then melt-mixed and extruded on a twin-screw extruder at 140° C. to 160° C. to obtain a target product.

6. The method for preparing a sericin-based fully biodegradable composite film material according to claim 5, characterized in that: The fully biodegradable plastic base includes PBAT, PLA or a mixture of the two.

7. The method for preparing a sericin-based fully biodegradable composite film material according to claim 5, characterized in that: The sericin includes unhydrolyzed sericin and hydrolyzed sericin.

8. The method for preparing a sericin-based fully biodegradable composite film material according to claim 5, characterized in that: The additives include one or two or more of water, glycerol, chain extender ADR, polyethylene glycol 400, maleic anhydride grafted modified PBAT, and glycidyl methacrylate / maleic anhydride copolymer grafted modified PBAT.

9. The method for preparing a sericin-based fully biodegradable composite film material according to claim 5, characterized in that: The sericin is modified sericin, and the modification method thereof comprises: a. Silk degumming under high temperature and high pressure: degumming the raw silk, and taking the degumming liquid after the degumming is completed; b. Preparation of pure sericin powder: The collected degumming liquid was rotary evaporated at 80°C to obtain sericin concentrate, which was then powdered using a spray dryer; c. Preparation of modified sericin: sericin powder, sodium sulfite and urea solution were mixed and pretreated with magnetic stirring in a water bath at 50°C for 30 minutes; after the temperature was raised to 80°C, a certain amount of glycidyl methacrylate and initiator ammonium persulfate were added, and the reaction was kept warm for several hours to generate modified sericin; the product was first washed with acetone and centrifuged twice, and then repeated with anhydrous ethanol twice at a speed of 4000r / min for 10min; after filtration, the filter cake was vacuum dried at 40°C for 12h and then sealed for storage.

10. The method for preparing a sericin-based fully biodegradable composite film material according to claim 9, characterized in that: In step b, the spray dryer is used to prepare powder, and the air inlet temperature is set to 180° C., the air outlet temperature is set to 80-85° C., and the centrifugal speed is set to 24000 r / min.